Studies on the analysis of benzo(a)pyrene and its metabolites in biological samples by using high performance liquid chromatograpy/fluorescence detection and gas chromatography/mass spectrometry - Lee, W; Shin, HS; Hong, JE; Pyo, H; Kim, Y (KOREAN CHEMICAL SOC, 2003)
An analytical method the determination of benzo(a)pyrene (BaP) and its hydroxylated metabolites, 1-hydroxybenzo(a)pyrene (1-OHBaP), 3-hydroxybenzo(a)pyrene (3-OHBaP), benzo(a)pyrene-4,5-dihydrodiol (4,5-diolBaP) and benzo(a)pyrene-7,8-dihydrodiol (7,8-diolBaP), in rat urine and plasma has been developed by HPLC/FLD and GC/MS. The derivatization with alkyl iodide was employed to improve the resolution and the detection of two mono hydroxylated metabolites, 1-OHBaP and 3-OHBaP, in LC and GC. BaP and its four metabolites in spiked urine were successfully separated by gradient elution on reverse phase ODS C-18 column (4.6 mm I.D., 100 mm length, particle size 5 mum) using a binary mixture of MeOH/H2O (85/15, v/v) as mobile phase after ethylation at 90 degreesC for 10 min. The extraction recoveries of BaP and its metabolites in spiked samples with liquid-liquid extraction, which was better than solid phase extraction, were in the range of 90.3-101.6% in n-hexane for urine and 95.7-106.3% in acetone for plasma, respectively. The calibration curves has shown good linearity with the correlation coefficients (R-2) varying from 0.992 to 1.000 for urine and from 0.996 to 1.000 for plasma, respectively. The detection limits of all analytes were obtained in the range of 0.01 - 0.1 ng/mL for urine and 0.1-0.4 ng/mL for plasma, respectively. The metabolites of BaP were excreted as mono hydroxy and dihydrodiol forms after intraperitoneal injection of 20 mg/kg of BaP to rats. The total amounts of BaP and four metabolites excreted in dosed rat urine were 3.79 ng over the 0-96 hr period from adminstration and the excretional recovery was less than 0.065% of the injection amounts of BaP. The proposed method was successfully applied to the determination of BaP and its hydroxylated metabolites in rat urine and plasma for the pharmacokinetic studies.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; MASS-SPECTROMETRY; BENZOPYRENE METABOLITES; PARTICULATE MATTER; URINARY-EXCRETION; RATS; 1-HYDROXYPYRENE; EXPOSURE